KOMPARASI ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY AKIBAT BOIKOT, DIVESTASI DAN SANKSI SEBELUM DAN SESUDAH KAMPANYE ALL EYES ON RAFAH - Rambe, M. Faiz Azhar; Prestianawati, Silvi Asna (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
The Israeli attack on the refugee camp in Rafah on May 26, 2024 gave rise to a campaign with the slogan “All Eyes on Rafah” and also encouraged people to join the BDS Movement against Israeli-affiliated companies. This study aims to analyze the differences in abnormal return and trading volume activity caused by the Boycott, Divestment, and Sanctions (BDS) Movement in Israeli-affiliated companies in the Indonesian Sharia Stock Index after the All Eyes on Rafah campaign. Based on signaling theory, an event can cause positive or negative reactions that will cause market reactions. Research with quantitative methods and event study approaches uses secondary data analyzed through the wilcoxon signed rank test processed with SPSS version 27 and Microsoft Excel. The analysis resulted in no significant difference in abnormal returns before and after the event but the market reacted negatively. trading volume activity has a significant difference between before and after the event.